Pelatihan Bermedia Digital bagi Siswa: Membangun Kesantunan Berbahasa di Media Sosial (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
This community service program aimed to improve students’ understanding and awareness of digital media ethics, particularly language politeness in social media communication. The activity was conducted at a junior high school in Islamic Boarding School Al Falah. The program was designed using participatory and interactive approaches, including lectures, group discussions, role-play simulations, and pre-test and post-test evaluations. The initial findings from the pre-test indicated that most students lacked adequate understanding of ethical digital communication and tended to perceive social media as a free space without rules. After the training, the post-test results showed a significant improvement in students’ comprehension of responsible and polite communication practices in digital environments. Students demonstrated better awareness of the impacts of hate speech, cyberbullying, and misinformation. They were also able to propose constructive and ethical responses to various social media scenarios. The activity resulted in increased digital awareness, positive behavioral changes, and personal commitments from students to promote respectful communication online. This program contributes to strengthening digital literacy and character education among adolescents in rural areas.